Not Everything is Black and Red: The Geographies of Canadian Economic Change - Barber, Rachel; Hartt, Maxwell (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2024)
Canada experienced the strongest economic growth of all G7 countries in 2022. However, economic development is not evenly distributed across the nation. Unlike global cities, economically declining municipalities are often overlooked, contributing to social, cultural, and political repercussions. What are the geographies of regional economic change in Canada? And what demographic and spatial characteristics are associated with economic decline? This study examines the spatial distribution of economic change across Canadian cities and regions from 1981 to 2021, while accounting for municipal boundary adjustments between census periods. The findings of our spatial analyses reveal distinct, complex patterns of socio-economic change, influenced by peripherality at various spatial scales. For instance, cities further from the American border were often found to have experienced undesirable trends in educational attainment and average income, while also experiencing an improvement in unemployment rates. These observations were confirmed through statistical analyses, with stagnation in educational attainment and income trends occurring in rural, peripheral, and demographically shrinking municipalities. Conversely, there is a positive relationship between trends in unemployment rates and population size. The diversity of geographies of economic change demonstrates the need for targeted interventions to mitigate the unique manifestations of decline within communities.